Improvement of tilapia (Oreochromis niloticus) patty using malunggay (Moringa oleifera) powder. - Frayco, Altia Narvaja
The study focused on the improvement of the tilapia patty using malunggay powder. Aside from the physical appearance of the tilapia, pH and total volatile base nitrogen (TVB-N) were measured to ensure freshness of fish. Tilapia had a mean pH of 6.32, with 0.810 mg of TVB-N. Three different formulations with varying amounts of malunggay powder, (5%, 10% and 15% of the tilapia meat) were subjected to preference rank sum test and general acceptability (7-point hedonic Scale) test. Tilapia-malunggay patty with 5% malunggay powder consistently ranked first among the three formulations. Total ranks of the tilapia-malunggay patties from the three formulations had significant difference (Kramer?s test, α = 0.05). In the general acceptability test, two (2) out of three (3) trials showed significant differences in the acceptability ratings of the tilapia-malunggay patties (Kruskal-Wallis test at α=5). Tilapia-malunggay patty with 5% malunggay powder was rated like moderately. Based on the results, the tilapia-malunggay patty with 5% malunggay powder was the most preferred formulation. The tilapia-malunggay patty from this formulation designated as TMPF was subjected to further analysis which included pH measurement, proximate analysis and mineral content determination. The TMPF had a mean pH of 5.84. It had a moisture content of 67.88%, crude protein of 13.02%, 2.44% crude ash, 2.62% of crude fat, 0.12% crude fiber and 13.92% carbohydrates. Addition of 5% malunggay powder increased the iron content from 3.2 mg/100g to 5.6 mg/100g and calcium content from 400 mg/100g to 1200 mg/100g of the tilapia patty. The calcium content of TMPF was significantly higher compared to the tilapia patty without malunggay powder (control) (T-test, (α=0.05). TMPF were characterized as brownish green, with slight malunggay odor, moderate to strong malunggay flavor, tender, firm to moderately tender, firm and slightly juicy. The product has market potential. Out of ninety (90) respondents, 75.56% rated the product like very much, 21.115 like moderately, 2.22% like slightly and 1.11% neither like nor dislike.